2017
DOI: 10.1016/j.compfluid.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of modelling choices on combustion in narrow channels

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights • Systematic analysis of modelling choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…For those variables displaying monotonic convergence, the recommendations of Stern at al. (2001) [29,30] were followed with the calculated grid convergence indices suggesting that the finest grid should match the Richardson extrapolated value of an infinitely refined grid to within 0.2%. For those displaying oscillatory convergence, the method in [29] requires an additional solution.…”
Section: Iiii 22 Computational Meshesmentioning
confidence: 99%
“…For those variables displaying monotonic convergence, the recommendations of Stern at al. (2001) [29,30] were followed with the calculated grid convergence indices suggesting that the finest grid should match the Richardson extrapolated value of an infinitely refined grid to within 0.2%. For those displaying oscillatory convergence, the method in [29] requires an additional solution.…”
Section: Iiii 22 Computational Meshesmentioning
confidence: 99%
“…While displaying convergent behaviour, the variables were not universally monotonic. For those variables displaying monotonic convergence, the recommendations of Stern et al (2001) (employed by Kang et al (2017)) were followed with the calculated grid convergence indices suggesting that the finest grid should match the Richardson extrapolated value of an infinitely refined grid to within 0.2%. For those displaying oscillatory convergence, the method of Stern et al (2001) requires an additional solution.…”
Section: Computational Meshesmentioning
confidence: 99%
“…Additionally, results from the transient simulations allowed for the observation of oscillations in simulation parameters (temperature), at operating conditions close to flame extinction; these oscillations were used to identify the stability limits of combustor configurations considered. Finally, low wall thermal conductivity was observed to reduce the heat transfer in the post flame region, which in turn served to reduce the heat recirculation and preheating of the reactants in the pre-flame zone A computational investigation by Kang et al [8] From the results, it was concluded that 'auto-ignition' (the natural ignition of the reactants as a result of a sufficiently high ignition temperature) might not be possible, for cases considering CHT, due to the inability to generate the critical quantity of radicals necessary to sustain combustion. To counteract the failed ignition, during the investigation a pre-simulated flow with one tenth of the mass flow rate of the combustion simulation, the preheating served to allow for ignition utilising the auto-ignition method.…”
Section: Microcombustor Simulation and Modellingmentioning
confidence: 99%
“…The simulated model considered the domain depicted in Figure 13. Simulation parameters, detailed in Table 6, were selected in accordance with those presented in [8], serving to recreate variations on the work produced by Chambers [19], which would further verify the performance of the orthotropic module; as well as provide external data for comparison. It should also be noted that the simulations considered were run on a relatively coarse mesh, Lastly, the various configuration options for the simulation parameters were maintained for the comparison, with the configuration options selected reflective of the simulation domain and boundary conditions proposed in Figure 13, with the most notable being the use of the Euler time step method (which is 1 st order accurate in time); refer to Appendix A & B for the specific configuration options.…”
Section: Initial Microcombustor Simulation 61 Simulation Definitionmentioning
confidence: 99%